STRESS RELATED TO TRAUMATIC SCAR POST FACIAL INJURIES: AN ORIGINAL RESEARCH (Journal of Pharmaceutical Negative Results, 2022)
Aim: Purpose of the present research was to assess the amount of stress and anxiety related to post facial injuries scarring in patients.Methodology: PTSD was assessed one month postoperatively by the diagnostic instrument, IES-R, to arrive at a provisional diagnosis. A structured clinician-administered PTSD Scale then assessed the patients for the Diagnostic and Statistical Manual of Mental Disorders-5th edition (CAPS-5) to establish a final diagnosis. The assessment of the severity of PTSD was done based on various types of oral and maxillofacial injuriesResults: The IES-R scale provisionally diagnosed 54 subjects with PTSD, out of which 42 were diagnosed to have PTSD by the CAPS-5 scale. Subjects with injuries involving the ‘orbital complex,’ those presenting with a perceptible scar in the maxillofacial region and with multiple avulsed/ luxated anterior teeth, showed a higher affinity to develop PTSD, and this was statistically significant.Conclusion: Higher levels of PTSD in patients with injuries to the maxillofacial region warrants correct diagnosis and detection, and hence the maxillofacial surgeon plays a vital role in this regard.